2014
DOI: 10.17306/j.afs.2014.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxidation and heme catalysis in coloration of raw meat

Abstract: Lipid peroxidation (LPO) alongside with other processes of post mortem metabolism is decisive for quality formation of meat products. Phenomena encountered in meat raw materials as a result of LPO can be summarized under three headings: 1 -those affecting safety (formation of malonic dialdehyde, fatty acids peroxides, oxidized cholesterol etc); 2 -those affecting biological value (lowering the content of non-replaceable fatty acids and vitamins, oxidative amino-acid decomposition, decrease of protein digestibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Haem protein has the ability to speed up the decomposition of peroxides, resulting in the formation of secondary aldehydic lipid oxidation products. When haem proteins like haemoglobin or myoglobin interact with lipid hydroperoxides, they cause the hydroperoxide to decompose into free radicals or reactive aldehyde compounds (Maestre et al., 2009; Shleikin and Medvedev, 2014; Chaijan and Panpipat, 2017). Although the PV of dorsal muscle was lower than that of ventral muscle ( P < 0.05), their TBARS content was comparable ( P > 0.05) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Haem protein has the ability to speed up the decomposition of peroxides, resulting in the formation of secondary aldehydic lipid oxidation products. When haem proteins like haemoglobin or myoglobin interact with lipid hydroperoxides, they cause the hydroperoxide to decompose into free radicals or reactive aldehyde compounds (Maestre et al., 2009; Shleikin and Medvedev, 2014; Chaijan and Panpipat, 2017). Although the PV of dorsal muscle was lower than that of ventral muscle ( P < 0.05), their TBARS content was comparable ( P > 0.05) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The high tendency of unsaturated fatty acids, especially polyunsaturated fatty acids, to rapidly oxidize is important in further biochemical changes that have undesirable effects, such as rancidity and color deterioration (Wood and others ). The unsaturated fatty acyl group of phospholipids from muscle fiber membranes (sarcolemma, mitochondria, and sarcoplasmic reticulum) is the 1st to be oxidized (Morrissey and others ; Shleikin and Medvedev ). Turkki and Campbell () have studied the distribution of phospholipids in 2 beef muscles and suggested that in both muscles lecithin accounted for about 62%, cephalins for 30%, and sphingomyelins for less than 10%.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…More studies were undertaken to determine in which form iron is responsible for the catalysis of the lipid peroxidation in meat and meat products. In experimental models with various meat species, such as beef and fish, many researchers have indicated that iron from meat heme proteins plays a crucial role in catalysis of lipid peroxidation (Rhee and Ziprin ; Min and Ahn ; Min and others ; Gheisari and others ; Shleikin and Medvedev ). Rhee and Ziprin () studied lipid peroxidation, myoglobin concentration, and total pigment in pork, beef, and chicken raw muscles during 2 to 6 d of storage and they concluded that the lipid peroxidation intensity was dependent on animal species and muscle type.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Mb oxidized to the brown MetMb form and its accumulation is highly correlated with the progression of lipid peroxidation (LPO), another process of post mortem metabolism that is decisive for meat quality. Indeed, the pseudoperoxidase activity of MetMb that catalyses the oxidation of various compounds in the presence of H 2 O 2 is highly correlated with LPO progression, which is one of the main factors limiting the quality and acceptability of meat …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the pseudoperoxidase activity of MetMb that catalyses the oxidation of various compounds in the presence of H 2 O 2 15,16 is highly correlated with LPO progression, which is one of the main factors limiting the quality and acceptability of meat. 11,17…”
Section: Introductionmentioning
confidence: 99%